Nicaragua : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2010)
This poverty reduction strategy paper on Nicaragua shows that the main obstacles to poverty reduction are related to culture, historical, and structural factors, as well as weak public policy. The lack of proper physical infrastructure, the weaknesses in the energy matrix, the flaws in the health, education, and potable water systems, and the precarious presence of state institutions in the territory have all contributed to the lack of success in poverty reduction. The country's potential in agriculture and natural resources are the main areas of opportunity regarding economic growth and poverty reduction.